In silico analysis of wild-type and mutant KRAS - Frengki Frengki; Dedi Prima Putra; Fatma Sriwahyuni; Daan Khambri; Henni Vanda (Pharmaciana, 2019)
The mutations of the KRAS gene at codons 12, 13, and 61 have been widely reported with different prognosis. In silico is one approach to explain the characteristics of the mutant genes. This study aimed to reveal the potential energy and fluctuations of the binding site and active site of wild-type KRAS (KRAS Wt) and mutant KRAS (KRAS Mt) at codons 12, 13, and 61. The samples used in this study were the sequences of KRAS Wt and KRAS Mt genes, which were subjected to in-silico analysis that included molecular homology, docking, and dynamics using MOE, PyMOL, and online CABS servers. The results showed that fluctuations in the binding site of all KRAS Mt were lower than that of KRAS Wt. On the contrary, the active site (switch I and switch II) of KRAS Mt fluctuated more widely than KRAS Wt. The potential energy of KRAS Mt before forming a complex with GTP was higher (p<0.01) than KRAS Wt. After this formation, it remained higher at codons 12 and 61 but lower at codons 11 and 13 (p <0.001). Mt G12A did not show any changes. The higher fluctuations in the switch I and switch II regions and the post energy of KRAS-GTP complexes may explain why types of cancers with mutations at codons 11 and 13 have a better prognosis than those with mutations at codons 12 and 61.